CREATIVITY AND INNOVATION IN PUBLIC RELATIONS, AS AN IMPORTANT TOOL IN ASSISTING MANAGERIAL DECISIONS - Gurgu, Elena; Zorzoliu, Raluca; Gurgu, Ioana-Andreea; Ilisie, Maria Gabriela (Annals of Spiru Haret University. Economic Series, 2022)
In this study, we write regarding creativity and innovation in public relations, of which it is evident that we need as a necessary means in supporting managerial judgments. For us, creativity in public relations can be a new way to achieve a goal easier, more efficient and faster. It is evident that every client acknowledges creativity, but in frequent situations, it does not convert into evident cases or messages for a mass audience and then is not visible. We also discuss in our study the profile of a ingenious public relations professional, who must be: engaged, instructed, ambitious for performance, having logical knowledge, having malleable and decisive judgment, being an idealist. In this analysis we will make an investigation to show that ingenuity can appear in one of the subsequent positions at the corporate administration zone: either in planning (positioning, outlining) or implementation (technique, presentation information, knowledge).